Implications of an Air Force Budget Downturn on the Aircraft Industrial Base An Exploratory Analysis - Arena, Mark V. (RAND Corporation, 2013)
The U.S. Air Force is facing a number of challenges as a result of the current defense budget downturn along with the uncertainty of its timing and magnitude. RAND examined the challenge of modernizing the Air Force's aircraft fleet while trying to sustain the industrial base with limited funding, considering six budget strategies for aircraft procurement: from a new high-tech fleet to sustaining and modifying the existing one.